Metal oxide supported carbon aerogel material, method for preparing same and use thereof
Patent Information
- Application Number
- CN202611130127.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本申请的主要目的是提出一种金属氧化物负载型炭气凝胶材料的制备方法及金属氧化物负载型炭气凝胶材料,以解决现有技术中炭气凝胶材料比表面积低、负载金属氧化物时易团聚而导致对气体污染物(如碳氧化物)吸附和催化转化性能受限的技术问题
[0004]本申请的主要目的是提出一种金属氧化物负载型炭气凝胶材料的制备方法及金属氧化物负载型炭气凝胶材料,以解决现有技术中炭气凝胶材料比表面积低、负载金属氧化物时易团聚而导致对气体污染物(如碳氧化物)吸附和催化转化性能受限的技术问题。
Smart Images

Figure CN122955458A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of porous adsorption catalytic materials technology, and in particular to a metal oxide supported carbon aerogel material, its preparation method and application. Background Technology
[0002] Against the backdrop of continuously rising global carbon emissions, the need for efficient pollution control technologies is urgent. The treatment of existing gaseous pollutants, such as carbon oxides (COX), faces challenges. Carbon aerogel materials, due to their porous structure, have been considered for use as adsorption or catalytic supports. However, traditional carbon aerogel materials often suffer from insufficient specific surface area, resulting in limited physical adsorption capacity for gases. While directly introducing metal oxides can provide chemical activity, simple composite methods easily lead to the agglomeration of metal oxide particles, reducing active sites and potentially further clogging the pores of the carbon aerogel, compromising its inherent high specific surface area advantage, and ultimately affecting the overall adsorption and catalytic conversion performance for gaseous pollutants.
[0003] Therefore, the key to improving the high-efficiency adsorption and catalytic conversion performance of carbon aerogel composite materials with both high specific surface area and high dispersion and uniform loading of metal oxides is to develop a carbon aerogel composite material with both high specific surface area and high dispersion and uniform loading of metal oxides. Summary of the Invention
[0004] The main objective of this application is to propose a method for preparing metal oxide-supported carbon aerogel materials and the metal oxide-supported carbon aerogel materials themselves, in order to solve the technical problems in the prior art where the carbon aerogel materials have low specific surface area and are prone to agglomeration when supported with metal oxides, which limits their adsorption and catalytic conversion performance for gaseous pollutants (such as carbon oxides).
[0005] To achieve the above objectives, in a first aspect, this application proposes a method for preparing a metal oxide-supported carbon aerogel material, comprising: Step S1, providing a carbon aerogel precursor; Step S2: The carbon aerogel precursor is mixed with potassium hydroxide solid and heat-treated under a first inert atmosphere. After washing, carbon aerogel is obtained. Step S3: Mix the carbon aerogel with copper nitrate solid, add a first solvent to wet the mixture, remove the solvent, and then perform pyrolysis treatment under a second inert atmosphere to obtain the metal oxide supported carbon aerogel material.
[0006] In some embodiments, the preparation method of the carbon aerogel precursor includes: mixing an organic carbon source, a crosslinking agent and a second solvent to form a carbon precursor solution, aging and drying it, and then carbonizing it under a third inert atmosphere to obtain the carbon aerogel precursor.
[0007] In some embodiments, the organic carbon source includes resorcinol and furfural; The crosslinking agent includes hexamethylenetetramine; The second solvent includes ethanol; The mass / volume ratio of resorcinol, furfural, crosslinking agent, and second solvent is 2:5:0.2:10.
[0008] In some embodiments, the aging treatment is performed at a temperature of 70-80°C for 5-9 days. The drying temperature is 80~100℃, and the time is 20~28 hours; The third inert atmosphere includes at least one of argon and nitrogen; The carbonization process involves heating to 800-950°C at a heating rate of 3-6°C / min and holding at that temperature for 2-3 hours.
[0009] In some embodiments, in step S2, the mass ratio of the carbon aerogel to the potassium hydroxide solid is 1:5.
[0010] In some embodiments, in step S2, the carbon aerogel precursor is ground and mixed with the potassium hydroxide solid to obtain a solid mixture, which is then wetted with a third solvent; the third solvent includes water and / or ethanol, and the mass ratio of the third solvent to the solid mixture is 0.6 to 1:1. The first inert atmosphere includes at least one of argon and nitrogen; The heat treatment includes heating to 700-800°C at a heating rate of 3-6°C / min and holding at that temperature for 0.5-1 hour; The washing process involves washing with deionized water until the solution is neutral.
[0011] In some embodiments, in step S3, the amount of copper nitrate solid used, based on the mass of the metal element, is 10% to 30% of the mass of the carbon aerogel; The second inert atmosphere includes at least one of nitrogen and argon; The pyrolysis treatment includes heating to 170-220°C at a heating rate of 3-5°C / min and holding at that temperature for 2-3 hours.
[0012] Secondly, this application also proposes a metal oxide-supported carbon aerogel material, which is prepared using the preparation method of the metal oxide-supported carbon aerogel material proposed in the first aspect of this application.
[0013] In some embodiments, the metal oxide-supported carbon aerogel material includes a carbon aerogel framework and copper oxide nanoparticles in situ supported on the carbon aerogel framework.
[0014] Thirdly, this application also proposes a method for preparing metal oxide-supported carbon aerogel materials as proposed in the first aspect of this application, and the application of metal oxide-supported carbon aerogel materials as proposed in the second aspect of this application in the adsorption and / or catalytic conversion of gaseous pollutants. The gaseous pollutants include carbon oxides.
[0015] The method for preparing metal oxide-supported carbon aerogel materials proposed in this application involves introducing solid potassium hydroxide for activation after carbonization. The intense etching effect of potassium hydroxide on the carbon framework at high temperatures creates numerous micropores and mesopores in the carbon aerogel, significantly increasing its specific surface area. This high specific surface area provides abundant attachment sites for subsequent metal loading and also offers greater capacity for the physical adsorption of gaseous pollutants. Secondly, a strategy is employed where the high specific surface area carbon aerogel is directly mixed with solid copper nitrate powder, wetted with only a small amount of solvent, and then the solvent is removed before in-situ pyrolysis. This method maximally restricts the free migration and aggregation tendency of metal ions in the liquid phase. During the subsequent pyrolysis, copper nitrate decomposes in-situ on the high specific surface area carbon aerogel framework to generate copper oxides. The high specific surface area and abundant porous structure of the carbon aerogel effectively immobilize the decomposition products, promoting the highly dispersed loading of copper oxides in nanoparticle form on the framework surface, providing a large number of uniformly distributed chemically active sites. Therefore, the material prepared by this method combines the excellent physical adsorption capacity brought by the high specific surface area carbon aerogel with the catalytic conversion activity provided by the highly dispersed copper oxide nanoparticles, thereby synergistically enhancing the comprehensive purification performance of gaseous pollutants (such as carbon oxides). Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0017] Figure 1 This is a schematic diagram illustrating the preparation of the metal oxide-supported carbon aerogel material provided in this application; Figure 2 This is a scanning electron microscope (SEM) image of the high specific surface area carbon aerogel material prepared in Example 1 of this application; Figure 3 This is a photograph of the metal oxide-supported carbon aerogel material prepared in Example 2 of this application. Figure 4 This is a scanning electron microscope (SEM) image of the metal oxide-supported carbon aerogel material prepared in Example 2 of this application; Figure 5 Thermogravimetric analysis (TGA) diagram of the metal oxide-supported carbon aerogel material prepared in Example 2 of this application; Figure 6 The XRD patterns are of the aerogel materials prepared in Examples 1, 2, and 3 and Comparative Example 1 of this application. Figure 7 The CO2 isotherm adsorption curves of the aerogel materials prepared in Examples 1, 2, 3 and Comparative Example 1 of this application at 298 K are shown. Figure 8 The above are CO-TPD temperature-programmed desorption curves of the aerogel materials prepared in Examples 1, 2, 3 and Comparative Example 1 of this application.
[0018] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0020] It should be noted that if the embodiments of this application involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0021] Furthermore, if the embodiments of this application involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution that simultaneously satisfies A and B. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed in this application.
[0022] With global carbon emissions continuing to rise and the climate and environmental crisis intensifying, the "dual carbon" goal urgently demands efficient carbon emission control technologies. Existing adsorbents generally suffer from problems such as small physical adsorption capacity and low chemical adsorption efficiency. For example, precious metal adsorption catalysts are expensive and prone to poisoning; while metal oxide adsorption catalysts show potential, they suffer from problems such as easy aggregation and few activation sites, thus limiting their catalytic activity. Carbon aerogels, as porous supports, often have their adsorption performance limited by their low specific surface area.
[0023] Based on the above problems, in a first aspect, embodiments of this application propose a method for preparing a metal oxide-supported carbon aerogel material, comprising: S1, providing carbon aerogel precursors; S2. The carbon aerogel precursor is mixed with potassium hydroxide solid and heat-treated under a first inert atmosphere. After washing, carbon aerogel is obtained. S3. The carbon aerogel is mixed with copper nitrate solid, and after wetting with the first solvent, the solvent is removed. Then, it is subjected to pyrolysis treatment under a second inert atmosphere to obtain a metal oxide supported carbon aerogel material.
[0024] By directly mixing the carbonized aerogel with solid potassium hydroxide and then subjecting it to activation heat treatment, a dense network of micropores and mesopores is constructed within the carbon matrix through the vigorous etching reaction between potassium hydroxide and the carbon framework at high temperatures. Subsequent washing effectively removes residual alkali metals and reaction byproducts, ensuring the formation of clean pores. The resulting carbon aerogel exhibits a significantly increased specific surface area. This high specific surface area structure not only provides numerous physical adsorption sites for gaseous pollutants but also prepares ample adhesion surfaces for subsequent loading of metal oxides.
[0025] In the subsequent loading process, the high specific surface area carbon aerogel is directly mixed with, wetted, and rapidly dried with solid copper nitrate. This process restricts the free migration and re-aggregation of copper ions in the solvent. During the subsequent pyrolysis treatment under an inert atmosphere, copper nitrate decomposes in situ within the porous structure of the carbon framework. The resulting copper oxide nanoparticles are effectively anchored on the carbon aerogel framework, achieving highly dispersed loading and avoiding the metal particle agglomeration and pore blockage problems common in traditional liquid-phase impregnation methods. Therefore, the preparation method of this application synergistically integrates the physical adsorption function of high specific surface area carbon aerogel and the chemical catalytic function of highly dispersed copper oxide nanoparticles.
[0026] To obtain a uniform and stable initial carbon framework, in some embodiments, the preparation method of the carbon aerogel precursor includes: mixing an organic carbon source, a crosslinking agent, and a second solvent to form a carbon precursor solution; aging and drying the solution; and then carbonizing it under a third inert atmosphere to obtain the carbon aerogel precursor. After the organic carbon source and crosslinking agent are thoroughly mixed in the solvent, the crosslinking agent promotes the crosslinking reaction between organic carbon source molecules, forming a wet gel network. Through a predetermined aging process, the gel network is strengthened. During the drying step, atmospheric pressure drying is used when removing the solvent, and capillary forces are balanced by controlling the temperature and time to maintain the integrity of the pore structure. Finally, the carbonization treatment under an inert atmosphere transforms the organic gel into a carbon aerogel precursor with excellent conductivity, thermal stability, and chemical stability.
[0027] To further improve the crosslinking efficiency of the carbon precursor and the orderliness of the carbon skeleton structure in step S1, in some embodiments, the organic carbon source includes at least one of resorcinol and furfural; the crosslinking agent includes hexamethylenetetramine; and the second solvent includes ethanol.
[0028] Resorcinol and furfural, as dual organic carbon source precursors, exhibit high reactivity and can undergo an effective sol-gel transition in an alkaline environment using hexamethylenetetramine as a crosslinking agent, forming a three-dimensional network structure. Ethanol, as a solvent, can effectively dissolve the aforementioned organic source and crosslinking agent. Due to its low surface tension, ethanol helps to mitigate the collapse of the pore structure during subsequent drying, maintaining the integrity of the gel framework. Furthermore, since furfural is only slightly soluble in water, the use of ethanol ensures that its residue is minimized.
[0029] In one embodiment, a combination of resorcinol and furfural is selected as the organic carbon source, hexamethylenetetramine is selected as the crosslinking agent, and ethanol is used as the solvent to prepare the precursor solution. Through subsequent processes, a carbon aerogel precursor with a uniform structure can be stably obtained, providing an excellent initial substrate for subsequent activation and loading.
[0030] To ensure the efficiency and quality of carbon framework construction, and to guarantee the sufficiency of the gelation reaction and drying process, in some embodiments, the mass / volume ratio of resorcinol, furfural, crosslinking agent, and second solvent is 2:5:0.2:10. If a uniform mass ratio is used, based on the density of anhydrous ethanol, its proportion can be adjusted to 8, i.e., the mass ratio of resorcinol, furfural, crosslinking agent, and second solvent is 2:5:0.2:8. Under this ratio, the solid content of the organic monomer and crosslinking agent is moderate, the sol-gel reaction rate is stable, and the degree of crosslinking of the formed wet gel network is appropriate. This ensures that the framework has sufficient strength to resist shrinkage during subsequent drying, without causing excessive brittleness due to over-crosslinking. Taking this ratio as an example, if 4g of resorcinol, 10mL of furfural, 0.4g of hexamethylenetetramine, and 20mL of ethanol are mixed and reacted at a suitable temperature, a uniform and transparent wet gel can be observed to gradually form. This proves that this ratio can construct an ideal precursor crosslinking network at the experimental level, laying the foundation for the microstructure and pore structure of the final carbon aerogel.
[0031] To ensure a stable carbon aerogel precursor with uniform pore size distribution, in some embodiments, the aging treatment temperature is 70-80°C for 5-9 days. For example, the aging treatment temperature can be 70°C, 75°C, or 80°C, and the time can be 5, 6, 7, 8, or 9 days. Preferably, the aging treatment temperature is 70°C for 7 days. Aging within this temperature range and time span promotes further cross-linking and maturation of the sol particles, increasing the mechanical strength of the gel skeleton. The drying temperature is 80-100°C for 20-28 hours. For example, the drying temperature can be 80°C, 85°C, 90°C, 95°C, or 100°C, and the time can be 20, 22, 24, 26, or 28 hours. Preferably, the drying temperature is 90°C for 24 hours. The third inert atmosphere includes argon. The carbonization process involves heating to 800-950°C at a rate of 3-6°C / min and holding at that temperature for 2-3 hours. For example, the heating rate can be 3°C / min, 4°C / min, 5°C / min, or 6°C / min, the final temperature can be 800°C, 850°C, 900°C, or 950°C, and the holding time can be 2 hours, 2.5 hours, or 3 hours. Preferably, the heating rate is 5°C / min, the final temperature is 900°C, and the holding time is 3 hours. Using an inert atmosphere such as argon during carbonization effectively prevents the carbon skeleton from oxidizing at high temperatures. With specific heating rates, final temperatures, and holding times, non-carbon elements in the organic precursor are gradually removed in small molecule form, ultimately forming a stable, pure carbon aerogel precursor with a certain initial porous structure.
[0032] In the activation process of step S2, to maximize the generation of micropores and mesopores on the carbon framework, in some embodiments, the mass ratio of carbon aerogel to potassium hydroxide solid is 1:5. This ratio provides sufficient chemical activator to ensure a sufficient etching reaction between potassium hydroxide and carbon atoms at high temperatures. Too little activator will result in insufficient pore formation and insignificant improvement in specific surface area; while exceeding this mass ratio may lead to over-etching of the carbon framework, causing thinning of the pore walls or even structural collapse, resulting in reduced strength and yield.
[0033] To ensure sufficient contact and uniform etching between the potassium hydroxide activator and the carbon aerogel framework, in some embodiments, step S2 involves: grinding the carbon aerogel precursor and mixing it with solid potassium hydroxide to obtain a solid mixture, then wetting it with a third solvent. The third solvent includes water and / or ethanol, with a mass ratio of 0.6 to 1:1 to the solid mixture. For example, the mass ratio of the third solvent to the solid mixture can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, or 1:1, etc. Pre-grinding the carbon aerogel precursor increases its contact area with potassium hydroxide. Wetting with a small amount of water or ethanol partially dissolves the potassium hydroxide, allowing it to be more uniformly adsorbed in ionic form and penetrate into the surface and internal pores of the carbon particles. After drying, it forms a tight coating on the carbon wall at the microscale.
[0034] The first inert atmosphere includes argon. The heat treatment involves heating to 700-800°C at a heating rate of 3-6°C / min and holding at that temperature for 0.5-1 hour. For example, the heating rate can be 3°C / min, 4°C / min, 5°C / min, or 6°C / min. The final temperature of the heat treatment can be 700°C, 750°C, or 800°C, and the holding time can be 0.5 hours, 0.8 hours, or 1 hour. Washing is performed with deionized water until neutral. Preferably, the heating rate of the heat treatment is 5°C / min, the final temperature of the heat treatment is 750°C, and the holding time is 30 minutes.
[0035] Under an inert argon atmosphere, heating the mixture at a rate of 3–6 °C / min ensures a uniform heat distribution and avoids bumpy reactions. Holding at 700–800 °C, the temperature range where potassium hydroxide reacts violently with carbon, for 0.5–1 hour is sufficient to ensure a complete and uncontrolled etching reaction. Finally, repeated washing with deionized water until neutral completely removes residual potassium salts and alkali metal impurities, yielding a pure carbon aerogel product with a high specific surface area.
[0036] To achieve high dispersion and controllable in-situ loading of copper oxide, in some embodiments, the amount of solid copper nitrate in step S3, based on the mass of the metal element, is 10% to 30% of the mass of the carbon aerogel. For example, the amount of solid copper nitrate, based on the mass of the metal element, is 10%, 15%, 20%, 25%, or 30% of the mass of the carbon aerogel. Preferably, the amount of solid copper nitrate, based on the mass of the metal element, is 20% of the mass of the carbon aerogel. The addition amount of 10% to 30% based on the mass of metallic copper ensures that a sufficient copper source is provided for the active sites, while avoiding waste of active components and excessive blockage of matrix pores due to excessive loading. Directly mixing and wetting the carbon aerogel with solid copper nitrate and then drying it greatly limits the long-distance migration of copper ions in the liquid phase.
[0037] In some embodiments, the second inert atmosphere includes nitrogen. The pyrolysis treatment involves heating to 170-220°C at a heating rate of 3-5°C / min and holding at that temperature for 2-3 hours. For example, the heating rate of the pyrolysis treatment is 3°C / min, 4°C / min, or 5°C / min, etc. The final temperature of the pyrolysis treatment is 170°C, 180°C, 190°C, 200°C, 210°C, or 220°C, etc. The holding time is 2 hours, 2.5 hours, or 3 hours, etc. Preferably, the heating rate of the pyrolysis treatment is 3°C / min, the final temperature of the pyrolysis treatment is 200°C, and the holding time is 2 hours.
[0038] Under an inert atmosphere such as nitrogen, a steady heating rate of 3-5℃ / min ensures uniform heat conduction, promoting the gradual and orderly decomposition of copper nitrate. Holding at 170-220℃ for 2-3 hours provides sufficient energy to completely convert copper nitrate into copper oxide, enabling it to form stable bonds with the carbon framework interface, generating uniformly dispersed nanoparticles without excessive sintering at high temperatures.
[0039] In some embodiments, in step S3, after adding the first solvent for impregnation, the solvent removal step includes water, and the mass ratio of the first solvent to the mixture is 1:1. Solvent removal can be carried out by atmospheric pressure drying at a temperature of 50-90°C for 20-28 hours. For example, the drying temperature can be 50°C, 60°C, 70°C, 80°C, or 90°C, and the drying time can be 20 hours, 22 hours, 24 hours, 26 hours, or 28 hours. Preferably, the drying temperature is 70°C and the drying time is 24 hours.
[0040] This application also proposes a metal oxide-supported carbon aerogel material, prepared using the method described above. The metal oxide-supported carbon aerogel material obtained by the method of this application necessarily inherits all the advantages of the method, namely, it simultaneously possesses the ultra-high specific surface area resulting from chemical activation and the highly dispersed metal oxide loading characteristics resulting from the solid premixing-in-situ pyrolysis strategy.
[0041] As a specific structural embodiment, metal oxide-supported carbon aerogel materials include a carbon aerogel framework and copper oxide nanoparticles in situ supported on the carbon aerogel framework. The carbon aerogel framework provides a three-dimensional continuous carbon network composed of numerous micropores and mesopores, playing a dual role of physical adsorption and mechanical support. The copper oxide nanoparticles are not simply physically filled into the pores, but are anchored to the surface of the carbon framework through chemical bonding or strong physical confinement effects. This in-situ generated and highly dispersed structural feature makes it difficult for the active metal oxide components to detach and aggregate, fully exposing the active surface. This, combined with the high specific surface area of the carbon aerogel, achieves the material design goal of integrating "adsorption-catalysis" functions.
[0042] In some embodiments, the specific surface area of the carbon aerogel framework is not less than 1000 m² / g, preferably not less than 1300 m² / g. The copper oxide is preferably copper oxide or a mixture of copper oxide and cuprous oxide, which is uniformly dispersed in the surface and pores of the carbon aerogel framework in at least one of the forms of nanowires, nanorods, and nanoparticles.
[0043] This application also proposes the application of a metal oxide-supported carbon aerogel material prepared by the method described above in the adsorption and / or catalytic conversion of gaseous pollutants. The gaseous pollutants include carbon oxides. Specifically, the carbon oxides are carbon monoxide, carbon dioxide, or mixtures thereof. The application specifically involves the removal of carbon monoxide and / or carbon dioxide from industrial flue gas, vehicle exhaust, or enclosed space air.
[0044] The metal oxide-supported carbon aerogel material in this embodiment exhibits excellent physical adsorption capacity due to its high specific surface area, enabling it to efficiently capture and enrich low concentrations of gas molecules such as CO2 from mixed gas streams. Simultaneously, its highly dispersed copper oxide nanoparticles serve as active centers, demonstrating strong chemical adsorption and catalytic oxidation activity towards CO and other gas molecules. When used to treat mixed gases containing CO and CO2, the carbon aerogel framework first enriches CO2 within its pores, while the copper oxide active sites catalyze the oxidation of CO to CO2. This synergistic mechanism of "adsorption enrichment-in-situ catalysis" makes it highly promising for applications involving carbon oxide emission control, such as industrial flue gas purification and indoor air treatment.
[0045] The following specific examples provide further details.
[0046] Example 1 This embodiment prepares carbon aerogel, referring to the preparation schematic diagram (e.g.) Figure 1 (As shown), the process is as follows: Take 4g of resorcinol and 10mL of furfural in a beaker, add 0.4g of hexamethylenetetramine and 20mL of ethanol, and stir in a 70℃ water bath for 30 minutes. Transfer the mixture to a PVC centrifuge tube, seal it, and age it in a 70℃ oven for 1 week to obtain the carbon aerogel precursor. After aging, dry the carbon aerogel precursor in a 90℃ oven at normal pressure for 24 hours. After drying, place the carbon aerogel precursor material in a high-temperature reactor and heat it to 900℃ at a rate of 5℃ / min under an argon atmosphere, and hold it at that temperature for 3 hours.
[0047] The carbonized carbon aerogel was thoroughly crushed and ground, and then uniformly mixed with KOH solid at a mass ratio of 1:5. A suitable amount of water and ethanol at a mass ratio of 1:1 to the solid mixture was added to aid in the dissolution of the KOH. The mixture was then transferred to an oven and dried at 70°C, and then placed back into a high-temperature reactor. Under an argon atmosphere, the temperature was increased to 750°C at a rate of 5°C / min and held for 30 minutes. Finally, the resulting material was thoroughly washed with deionized water until neutral and dried to obtain a high specific surface area carbon aerogel.
[0048] The carbon aerogel prepared in Example 1 was observed using a scanning electron microscope, and the results are as follows: Figure 2 As shown. From Figure 2 As can be seen, the carbon aerogel is composed of numerous interconnected carbon particles. Due to the etching reaction, the sample is filled with a large number of micropores. The specific surface area of the carbon aerogel obtained by this method is significantly improved. Compared with the specific surface area of traditional carbon aerogels, which is only a few hundred, the specific surface area of the sample in this embodiment reaches 1319.7 m². 2 / g.
[0049] Example 2 The preparation process of metal oxide-supported carbon aerogel material in this embodiment is as follows: The high specific surface area carbon aerogel from Example 1 was mixed with solid copper nitrate trihydrate (ensuring a copper nitrate loading of 20 wt%), and an appropriate amount of water was added to aid dissolution. The mixture was then dried in a 70°C oven. The dried mixture was placed in a quartz crucible and transferred together with the crucible to a tube furnace. Under a nitrogen atmosphere, the temperature was increased to 200°C at a rate of 3°C / min and held for 2 hours. The resulting metal oxide-supported carbon aerogel is shown in the image. Figure 3 As shown.
[0050] The metal oxide-supported carbon aerogel material prepared in Example 2 was observed using scanning electron microscopy, and the results are as follows: Figure 4 As shown. From Figure 4 It can be seen that in the metal oxide supported carbon aerogel material prepared in Example 2, some nanowire-shaped, rod-shaped and granular copper oxide crystals are loaded into the carbon aerogel.
[0051] Further thermogravimetric analysis was performed on the prepared metal oxide-supported carbon aerogel, and the results are as follows: Figure 5 As shown. From Figure 5 As can be seen, the sample mainly undergoes the removal of adsorbed water and residual solvent in the temperature range of room temperature to 150℃, while the decomposition of weakly oxygen-containing functional groups on the surface occurs between 150℃ and 300℃. After 300℃, the carbon skeleton begins to continuously oxidize and lose weight under the catalysis of CuO, and about 75 wt.% of the residual mass remains at 1000℃, mainly consisting of stable CuO components and some difficult-to-oxidize carbon residues. Overall, the material exhibits good thermal stability below 300℃, which can meet the requirements of medium and low temperature applications. At the same time, the introduction of CuO has a significant catalytic effect on the oxidation behavior of the carbon skeleton.
[0052] Example 3 The preparation process of metal oxide-supported carbon aerogel material in this embodiment is as follows: The high specific surface area carbon aerogel from Example 1 was mixed with solid copper nitrate trihydrate (ensuring a copper loading of 20 wt%), and an appropriate amount of water was added to aid dissolution. The mixture was then dried in a 70°C oven. The dried mixture was placed in a quartz crucible and transferred together with the crucible to a tube furnace. Under a nitrogen atmosphere, the temperature was increased to 300°C at a rate of 3°C / min and held for 2 hours. This yielded a metal oxide-supported carbon aerogel.
[0053] Example 4 Take 4g of resorcinol and 10mL of furfural in a beaker, add 0.4g of hexamethylenetetramine and 20mL of ethanol, and stir in a 70℃ water bath for 30 minutes. Transfer the mixture to a PVC centrifuge tube, seal it, and age it in a 70℃ oven for 1 week to obtain the carbon aerogel precursor. After aging, dry the carbon aerogel precursor in a 90℃ oven at normal pressure for 24 hours. After drying, place the carbon aerogel precursor material in a high-temperature reactor and heat it to 950℃ at a rate of 3℃ / min under an argon atmosphere, and hold it at that temperature for 2 hours.
[0054] The carbonized carbon aerogel was thoroughly crushed and ground, and then uniformly mixed with KOH solid at a mass ratio of 1:5. A suitable amount of water and ethanol at a mass ratio of 0.6:1 to the solid mixture was added to aid in the dissolution of the KOH. The mixture was then transferred to an oven and dried at 70°C, and then placed back into a high-temperature reactor. Under an argon atmosphere, the temperature was increased to 800°C at a rate of 3°C / min and held for 1 hour. Finally, the resulting material was thoroughly washed with deionized water until neutral and dried to obtain a high specific surface area carbon aerogel.
[0055] Carbon aerogel was mixed with solid copper nitrate trihydrate (ensuring a copper loading of 20 wt%), and an appropriate amount of water was added to aid dissolution. The mixture was then dried in a 70°C oven. The dried mixture was placed in a quartz crucible and transferred together with the crucible to a tube furnace. Under a nitrogen atmosphere, the mixture was heated to 220°C at a heating rate of 3°C / min and held at that temperature for 2 hours. This yielded a metal oxide-supported carbon aerogel.
[0056] Example 5 Take 4g of resorcinol and 10mL of furfural in a beaker, add 0.4g of hexamethylenetetramine and 20mL of ethanol, and stir in a 70℃ water bath for 30 minutes. Transfer the mixture to a PVC centrifuge tube, seal it, and age it in a 70℃ oven for 1 week to obtain the carbon aerogel precursor. After aging, dry the carbon aerogel precursor in a 90℃ oven at atmospheric pressure for 24 hours. After drying, place the carbon aerogel precursor material in a high-temperature reactor and heat it to 800℃ at a rate of 6℃ / min under an argon atmosphere, and hold it at that temperature for 3 hours.
[0057] The carbonized carbon aerogel was thoroughly crushed and ground, and then uniformly mixed with KOH solid at a mass ratio of 1:5. A suitable amount of water and ethanol at a mass ratio of 0.8:1 to the solid mixture were added to aid in the dissolution of the KOH. The mixture was then transferred to an oven and dried at 70°C, and then placed back into a high-temperature reactor. Under an argon atmosphere, the temperature was increased to 700°C at a rate of 6°C / min and held for 45 minutes. Finally, the resulting material was thoroughly washed with deionized water until neutral and dried to obtain a high specific surface area carbon aerogel.
[0058] Carbon aerogel was mixed with copper nitrate trihydrate solid (ensuring a copper loading of 20 wt%), and an appropriate amount of water was added to aid dissolution. The mixture was then dried in a 70°C oven. The dried mixture was placed in a quartz crucible and transferred together with the crucible to a tube furnace. Under a nitrogen atmosphere, the mixture was heated to 170°C at a heating rate of 5°C / min and held at that temperature for 3 hours. This yielded a metal oxide-supported carbon aerogel.
[0059] Comparative Example 1 Take 4g of resorcinol and 10ml of furfural in a beaker, add 0.4g of hexamethylenetetramine and 20ml of ethanol, and stir in a 70℃ water bath for 30min to ensure complete dissolution of hexamethylenetetramine and homogeneous mixing of the solution, thus preparing a precursor mixture solution. Transfer the mixture to a PVC centrifuge tube, seal it, and age it in a 70℃ oven for 1 week to obtain the carbon aerogel precursor material. After aging, dry the carbon aerogel precursor in a 90℃ oven at normal pressure for 24 hours. After drying, place the carbon aerogel precursor in a high-temperature reactor and heat it to 900℃ at a rate of 5℃ / min under an argon atmosphere, and hold it at that temperature for 3 hours. Thoroughly crush and grind the carbonized carbon aerogel, mix it with copper nitrate trihydrate solid (ensuring a copper nitrate loading of 20wt%), add an appropriate amount of water to aid dissolution, and then dry it in a 70℃ oven. The dried mixture was placed in a quartz crucible and transferred together with the crucible to a tube furnace. Under a nitrogen atmosphere, it was heated to 200°C at a heating rate of 3°C / min and held at that temperature for 2 hours. A composite material of unactivated carbon aerogel and metal oxide was obtained.
[0060] The specific surface areas of the carbon aerogel prepared in Example 1, the metal oxide-supported carbon aerogel materials prepared in Examples 2 and 3, and the composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1 were measured, and the results are shown in Table 1.
[0061]
[0062] As can be seen from Table 1, the specific surface area of the carbon aerogel prepared in Example 1 is as high as 1319.7 m². 2 / g, The metal oxide supported carbon aerogel materials prepared in Examples 2 and 3 inevitably had some of their original pore structures blocked due to the loading of copper oxide particles, resulting in a decrease in specific surface area, but it was still higher than the composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1.
[0063] X-ray diffraction analysis was performed on the carbon aerogel prepared in Example 1, the metal oxide-supported carbon aerogel materials prepared in Examples 2 and 3, and the composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1. The results are as follows: Figure 6 As shown. From Figure 6 It can be seen that the metal oxide-supported carbon aerogel materials prepared in Examples 2 and 3 achieved CuO loading. In Example 3, a small amount of Cu2O appeared in the metal oxide-supported carbon aerogel material. This is because the heat treatment temperature of 300°C is higher than the temperature at which copper nitrate is pyrolyzed to generate CuO, causing some CuO to be further converted into Cu2O.
[0064] The CO2 isothermal adsorption performance of the carbon aerogel prepared in Example 1, the metal oxide-supported carbon aerogel materials prepared in Examples 2 and 3, and the composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1 was tested at 298 K. The results are as follows: Figure 7 As shown. From Figure 7 It can be seen that the CO2 adsorption performance of the unactivated carbon aerogel-metal oxide composite material prepared in Comparative Example 1 is lower than that of the materials prepared in Examples 1-3. This indicates that the carbon aerogel in the material prepared in Comparative Example 1 was unactivated and loaded with CuO, resulting in a significantly lower specific surface area than the activated carbon aerogels in the other examples (as shown in Table 1), which is only 171.3 m². 2 / g. This further leads to its low CO2 adsorption capacity.
[0065] CO-TPD temperature-programmed desorption curves were tested on the carbon aerogel prepared in Example 1, the metal oxide-supported carbon aerogel materials prepared in Examples 2 and 3, and the composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1. The results are as follows: Figure 8 As shown. From Figure 8 It can be seen that the binding sites and binding strength of the metal oxide-supported carbon aerogel material prepared in Example 2 with CO gas molecules are much higher than those in Example 1 without CuO loading. This indicates that the preparation method provided in this application promotes the capture and adsorption process of CO gas molecules by loading CuO. The composite material of unactivated carbon aerogel and metal oxide prepared in Comparative Example 1 has a low CO2 adsorption capacity because the carbon aerogel has not undergone an activation process and is loaded with CuO. However, because the sample is loaded with CuO, its CO adsorption performance is still good.
[0066] Combined Figure 7 It can be seen that the CO2 adsorption capacity of the metal oxide supported carbon aerogel material prepared in Example 3 is slightly lower than that of the metal oxide supported carbon aerogel material prepared in Example 2, but the CO adsorption performance is still good.
[0067] In summary, in the preparation method of metal oxide supported carbon aerogel material proposed in this application, the introduction of the activation step is beneficial to increasing the specific surface area of the carbon aerogel, thereby improving the adsorption performance of the sample for CO2, and the introduction of CuO improves the adsorption performance of the material for CO.
[0068] The above description is merely an exemplary embodiment of this application and does not limit the patent scope of this application. Any equivalent structural transformations made based on the technical concept of this application and the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.
Claims
1. A method for preparing a metal oxide-supported carbon aerogel material, characterized in that, include: Step S1, providing a carbon aerogel precursor; Step S2: The carbon aerogel precursor is mixed with potassium hydroxide solid and heat-treated under a first inert atmosphere. After washing, carbon aerogel is obtained. Step S3: Mix the carbon aerogel with copper nitrate solid, add a first solvent to wet the mixture, remove the solvent, and then perform pyrolysis treatment under a second inert atmosphere to obtain the metal oxide supported carbon aerogel material.
2. The preparation method according to claim 1, characterized in that, The method for preparing the carbon aerogel precursor includes: mixing an organic carbon source, a crosslinking agent and a second solvent to form a carbon precursor solution, aging and drying it, and then carbonizing it under a third inert atmosphere to obtain the carbon aerogel precursor.
3. The preparation method according to claim 2, characterized in that, The organic carbon source includes resorcinol and furfural; The crosslinking agent includes hexamethylenetetramine; The second solvent includes ethanol; The mass / volume ratio of resorcinol, furfural, crosslinking agent, and second solvent is 2:5:0.2:
10.
4. The preparation method according to claim 2, characterized in that, The aging treatment is performed at a temperature of 70-80℃ for 5-9 days. The drying temperature is 80~100℃, and the time is 20~28 hours; The third inert atmosphere includes at least one of argon and nitrogen; The carbonization process involves heating to 800-950°C at a heating rate of 3-6°C / min and holding at that temperature for 2-3 hours.
5. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the carbon aerogel to the potassium hydroxide solid is 1:
5.
6. The preparation method according to claim 1, characterized in that, In step S2, the carbon aerogel precursor is ground and then mixed with the potassium hydroxide solid to obtain a solid mixture, which is then wetted with a third solvent; the third solvent includes water and / or ethanol, and the mass ratio of the third solvent to the solid mixture is 0.6~1:
1. The first inert atmosphere includes at least one of argon and nitrogen; The heat treatment includes heating to 700-800°C at a heating rate of 3-6°C / min and holding at that temperature for 0.5-1 hour; The washing process involves washing with deionized water until the solution is neutral.
7. The preparation method according to claim 1, characterized in that, In step S3, the amount of copper nitrate solid used, based on the mass of the metal element, is 10% to 30% of the mass of the carbon aerogel. The second inert atmosphere includes at least one of nitrogen and argon; The pyrolysis treatment includes heating to 170-220°C at a heating rate of 3-5°C / min and holding at that temperature for 2-3 hours.
8. A metal oxide-supported carbon aerogel material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The metal oxide-supported carbon aerogel material as described in claim 8, characterized in that: The metal oxide supported carbon aerogel material includes a carbon aerogel framework and copper oxide nanoparticles in situ supported on the carbon aerogel framework.
10. The application of the metal oxide supported carbon aerogel material prepared by the preparation method according to any one of claims 1 to 7, and the metal oxide supported carbon aerogel material according to claim 8 or 9, in the adsorption and / or catalytic conversion of gaseous pollutants; The gaseous pollutants include carbon oxides.